Sexual assault survivors' engagement with advocacy services during the COVID‐19 pandemic. Issue 6 (12th February 2022) - Engleton, Jasmine; Goodman‐Williams, Rachael; Javorka, McKenzie; Gregory, Katie; Campbell, Rebecca
Abstract: Sexual assault advocates provide support to survivors as they navigate medical, legal, housing, and other complex systems. However, social distancing measures enacted in response to coronavirus disease 2019 (COVID‐19) forced changes to traditional advocacy services. The current study aimed to understand how the COVID‐19 pandemic transformed survivors' engagement with sexual assault advocacy services. Semi‐structured interviews were conducted with 12 sexual assault advocates from a community‐based advocacy organization in Detroit. Thematic analysis was employed to uncover emergent themes reflecting COVID‐19's impact on survivors' engagement with advocacy services. Three themes were identified: (1) Disruption to advocacy services; (2) difficulty obtaining tangible resources; and (3) desire for COVID‐related support, information, and resources. This study highlights the needs of sexual assault survivors during the COVID‐19 pandemic and explores how public health emergencies have the potential to exacerbate the needs of this vulnerable population. Implications and future directions for service provision and research are considered.